Between 1980-1990 period the effects of interest rates on deposit banking as an marketing instrument and field resarch. - Draman, Zeynep (My University, 1990)
unknown
Keywords: BANKACILIK-PAZARLAMA; BANKACILIK-TÜRKİYE; Ekonomi; Finansman ekonomisi; Yatırım